2018
DOI: 10.3892/etm.2018.5945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-146a-5p on proliferation and metastasis of triple-negative breast cancer via regulation of SOX5

Abstract: Abstract. MicroRNA (miR)-146a-5p functions as a tumor suppressor in various types of cancer. However, the role of miR-146a-5p in the development of triple-negative breast cancer (TNBC) is unclear. The present study aimed to investigate the role of miR-146a-5p in TNBC. The expression level of miR-146a-5p in TNBC tissues and cell lines was initially detected using reverse transcription-quantitative polymerase chain reaction. To predict the target gene of miR-146a-5p, TargetScan software was used and a dual lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…The miR-199a-5p expression is significantly reduced in TNBC patients in comparison with other patients with non-TNBC breast cancer and a healthy group [42]. Also, other studies demonstrated that miR-199a-5p was associated with early stages of TNBC and miR-199a-5p may be a diagnostically valuable TNBC-specific marker in a large number of patients [43,89]. Savad et al showed that miR-205 and miR-342 expressions were significantly down-regulated in the TNBC group compared to other BC groups in 59 patients with breast cancer.…”
Section: Microrna-based Potential Diagnostic and Prognostic Implicatimentioning
confidence: 86%
See 1 more Smart Citation
“…The miR-199a-5p expression is significantly reduced in TNBC patients in comparison with other patients with non-TNBC breast cancer and a healthy group [42]. Also, other studies demonstrated that miR-199a-5p was associated with early stages of TNBC and miR-199a-5p may be a diagnostically valuable TNBC-specific marker in a large number of patients [43,89]. Savad et al showed that miR-205 and miR-342 expressions were significantly down-regulated in the TNBC group compared to other BC groups in 59 patients with breast cancer.…”
Section: Microrna-based Potential Diagnostic and Prognostic Implicatimentioning
confidence: 86%
“…Metastasis is a process in which tumor cell breaks away from the original site and travels through the blood or lymphatic system to the other parts of the body and form new tumors. Some miRNAs such as miR-146a-5p, miR-26a, miR-136 and miR-136 have been proved to inhibit the expression of numerous cancer-related genes that subsequently suppress metastasis in TNBC [43][44][45].…”
Section: Mirna-based Replacement Therapeutic Applications Suppress Mementioning
confidence: 99%
“…Furthermore, the miR-181a was involved in TNBC metastasis via elevated expression of Bim [72]. [115,116] miR-373 TXNIP Induces cancer cell EMT and metastasis [117,118] miR-10b HOXD10 Promotes invasion and metastasis [119] miR-21 PTEN Lymph node metastasis [120] miR-17/92 cluster COL4A3, LAMA3, TIMP2/3 Lymph node metastases, promote metastasis [121,122] miR-629-3p LIFR Lung metastases [123] miR-455-3p EI24 Promotes proliferation, invasion, and migration [124] miR-125b APC Promotes proliferation, metastasis, and EMT [125] miR-181a Bim Promotes EMT, migratory, and invasive [72] Oncosuppressor miRNAs miR-200a/b/c PKCα, UBASH3B, XIAP Suppress proliferation, migration, invasion, and metastasis, promote apoptosis [77,126,127] miR-205 Unknown Lymph node metastasis [128] let-7 RAS, c-Myc Block growth and reduce metastasis [129] miR-145 MUC1, Arf6, JAM-A, Fascin Reduce cell motility, invasiveness, and metastasis [130][131][132] miR-206 CORO1C Regulates metastasis [133] miR-30a ROR1 Associates with high histological grade and more lymph node metastasis [134] miR-190a/940 Unknown Prevents metastasis and cell invasion [19,135] miR-33b HMGA2, SALL4, Twist1 Inhibit metastasis [114] miR-146a-5p SOX5 Inhibits proliferation and metastasis [136] miR-150 HMGA2 Inhibits metastasis [137] miR-124 ZEB2 Inhibits invasion and metastasis [138] miR-148a WNT1, NRP1 Suppress metastasis [139] miR-126-3p RGS3 Inhibits proliferation, migration, invasion, and angiogenesis [140] miR-508-3p ZEB1 Inhibits cell invasion and EMT [141] miR-613 Daam1 Inhibits cell migration and invasion [142] miR-519d-3p LIMK1 Suppresses growth and mot...…”
Section: Mirnas In Regulation Of Metastasis In Tnbcmentioning
confidence: 99%
“…MiR-190a and miR-940 were also significantly reduced in TNBC tissues to prevent metastasis and cell invasion [19,135]. Additionally, several miRNAs function as oncosuppressor miRNAs involved in metastasis of TNBC, such as miR-33b [114], miR-146a-5p [136], miR-150 [137], miR-124 [138] and miR-148a [139], miR-126-3p [140], miR-508-3p [141], miR-613 [142], miR-519d-3p [143], miR-26a [144], and miR-130a [145], by targeting HMGA2, SALL4 and Twist1, SRY-box transcription factor 5 (SOX5), HMGA2, ZEB2, wnt family member 1 (WNT1) and neuropilin 1 (NRP1), the regulator of G-protein signaling 3 (RGS3), ZEB1, disheveled-associated activator of morphogenesis 1 (Daam1), LIM domain kinase 1 (LIMK1), metadherin (MTDH), FOSL1, and zonula occludens 1 (ZO-1, also called TJP1), respectively.…”
Section: Mirnas In Regulation Of Metastasis In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation